2008
DOI: 10.1111/j.1468-5906.2008.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Prayer, God Imagery, and Symptoms of Psychopathology

Abstract: Researchers have shown a longstanding interest in the relationship between religion and mental health. Here, we outline a series of hypotheses linking personal prayer, images of God, and mental health. We then empirically test the hypotheses using data from an online survey of U.S. adults (N = 1,629) conducted in 2004 by Spirituality and Health magazine. We find a positive correlation between both frequency of prayer and the perception of God as remote and several different forms of psychopathology; a perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 55 publications
4
80
0
2
Order By: Relevance
“…Another promising avenue of research could be to investigate how specific beliefs about the nature of God and the afterlife buffer against trauma (e.g., (Ellison et al 2001;Ellison et al 2009)). As mentioned earlier, we might expect persons who believe God is compassionate and forgiving to be more resilient in the face of trauma compared to those who view God as harsh or judgmental (Bradshaw et al 2008). We might also expect that people who fear hell or any other form of divine punishment will interpret stressful life events as significantly more ominous and suffer even greater distress as a result (Foley 1988;Exline et al 2000;Flannelly 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising avenue of research could be to investigate how specific beliefs about the nature of God and the afterlife buffer against trauma (e.g., (Ellison et al 2001;Ellison et al 2009)). As mentioned earlier, we might expect persons who believe God is compassionate and forgiving to be more resilient in the face of trauma compared to those who view God as harsh or judgmental (Bradshaw et al 2008). We might also expect that people who fear hell or any other form of divine punishment will interpret stressful life events as significantly more ominous and suffer even greater distress as a result (Foley 1988;Exline et al 2000;Flannelly 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, people who view God as harsh or judgmental tend to report greater depression and anxiety, especially when confronting stressful life events (Bradshaw et al 2008. Some believers might interpret traumatic life events as God punishing them for sins (Ellis 1960), which may cause them to grow hopeless and to feel that their only recourse is to resign to "God's Will" (Pargament et al 1988;Foley 1988).…”
Section: Potential Harms: Stress-exacerbating Hypothesismentioning
confidence: 99%
“…Studies have found secure attachment to and intimacy with God to be inversely associated with psychological distress and psychopathology (Bradshaw et al 2008;Bradshaw et al 2010), and positively associated with greater resilience after perceived negative events (Ellison et al 2014). Anxious attachment, in contrast, was positively correlated with psychiatric symptoms such as general and social anxiety, obsession, and compulsion (Ellison et al 2014).…”
Section: Religion and Attachment Theorymentioning
confidence: 99%
“…In fact, rival bodies of scholarship have emerged. One stream of research has indicated a persistently null association between prayer and mental health (Ellison 1991;Ellison et al 2009;Schieman et al 2006), while another has linked prayer to adverse mental health conditions (Bradshaw et al 2008;Ellison 1995;Ellison et al 2001) ).…”
Section: Empirical Backgroundmentioning
confidence: 99%